2017
DOI: 10.1002/stem.2661
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Challenges in Regenerating the Diabetic Heart: A Comprehensive Review

Abstract: Stem cell therapy is one of the promising regenerative strategies developed to improve cardiac function in patients with ischemic heart diseases (IHD). However, this approach is limited in IHD patients with diabetes due to a progressive decline in the regenerative capacity of stem cells. This decline is mainly attributed to the metabolic memory incurred by diabetes on stem cell niche and their systemic cues. Understanding the molecular pathways involved in the diabetes-induced deterioration of stem cell functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 196 publications
(241 reference statements)
0
12
0
Order By: Relevance
“…The association hyperglycemia/ROS/cellular senescence represents a major cause of inefficiency of regenerative medicine [9, 10, 56, 57]. Further, clinical trials established that an altered glycemic control is equal to therapeutic failure [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…The association hyperglycemia/ROS/cellular senescence represents a major cause of inefficiency of regenerative medicine [9, 10, 56, 57]. Further, clinical trials established that an altered glycemic control is equal to therapeutic failure [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the main cause of morbidity and mortality in diabetic patients, accounting for about 80% of all diabetic deaths in North America [ 214 , 215 ]. DM has a dramatic impact on the aging and senescence of different types of adult stem cells [ 216 ]. In particular, DM impairs the in vitro proliferative and differentiation potential of adult CSCs, further worsening their senescence phenotype even when compared with CSCs from non-diabetic ischemic patients [ 217 ].…”
Section: Csc Senescence and Diabetic Cardiomyopathymentioning
confidence: 99%
“…A pioneer work done by Salabei and co‐workers showed that HGC had prominent effect on CPCs glucose metabolism and glycolysis by modulating the activity of enzyme PFKFB3, contributed to a reduced mitochondrial activity . Uncontrolled glycolysis activation in CPCs elevates the generation of reactive oxygen species and accumulation of methylglyoxal, advanced glycation end product, inside CPCs . The occurrence of diabetic condition predisposes CPCs entering aging via the modulation of telomeric shortening and the activation of P53 and p16 INK4a .…”
Section: Discussionmentioning
confidence: 99%
“…29 Uncontrolled glycolysis activation in CPCs elevates the generation of reactive oxygen species and accumulation of methylglyoxal, advanced glycation end product, inside CPCs. [29][30][31] The occurrence of diabetic condition predisposes CPCs entering aging via the modulation of telomeric shortening and the activation of P53 and p16 INK4a . [32][33][34][35][36] In our previous work, a decrease in the total level of Akt factor was evident in EPCs after 7-day treatment with serum from diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%